2018
DOI: 10.1007/s10143-018-0968-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with spinal chordomas

Abstract: This study was aimed to analyze the survival of patients with spinal chordomas. Patients' data in the Surveillance, Epidemiology, and End Results (SEER) database were retrieved and analyzed statistically. There were 765 patients with spinal chordomas between 1974 and 2013. The overall survival did not improve significantly over decades for patients receiving surgery and radiotherapy (SR) (P = 0.221). There were significant differences in overall survival among subgroups of patients receiving surgery (S), radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The distant metastatic rate was 7.7%. These findings were very similar to those by Kerr et al examining 377 patients with sacral and spinal chordomas from the NCDB (2004-2015) and slightly higher than that reported by previous authors 34-38 . Pan et al found that age older than 60 years, distant metastasis, and nonsurgical therapy were associated with worse overall survival 33 .…”
Section: Clinical Presentation and Prognostic Factorssupporting
confidence: 91%
“…The distant metastatic rate was 7.7%. These findings were very similar to those by Kerr et al examining 377 patients with sacral and spinal chordomas from the NCDB (2004-2015) and slightly higher than that reported by previous authors 34-38 . Pan et al found that age older than 60 years, distant metastasis, and nonsurgical therapy were associated with worse overall survival 33 .…”
Section: Clinical Presentation and Prognostic Factorssupporting
confidence: 91%
“… 15 , 16 Based on the microscopic morphology, there are 3 different histological subtypes of spinal chordoma, including conventional, chondroid, and dedifferentiated. 12 Of all histological subtypes, the dedifferentiated type is the most aggressive subtype, which significantly affects prognosis. 17 Meanwhile, the results of this study showed that histological type had a significant effect on survival outcomes, once again confirming the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…As the International Classification of Tumor Histology, 3 rd edition states, chordoma can be classified as conventional, chondroid, and dedifferentiated. 12 Based on the American Joint Committee on Cancer TNM staging system (8th edition, 2016), tumor size is usually divided into 2 categories: ≤ 8.0 cm and > 8.0 cm. 13 For this follow-up study, the starting point was the date of diagnosis of the chordoma, while the endpoint CSS was the length of time from the date of diagnosis to the patient’s death due to the chordoma.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has also been pointed out that for spinal confned tumors, chemotherapy is one of the signifcant worsening infuences, while for spinal metastatic tumors, chemotherapy has a good therapeutic efect [18,29]. Unlike chemotherapy, radiotherapy is thought to have a signifcant tumor metastasis suppression efect, signifcantly reducing the probability of metastasis in the group of patients who receive radiotherapy immediately after surgery [30,31].…”
Section: Discussionmentioning
confidence: 99%